Pengaruh corporate governance dan karakteristik perusahaan terhadap luas pengungkapan corporate social responsibility (CSR) di dalam Sustainability Report - Dian Kusuma; Amries Rusli Tanjung; Edfan Darlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to examine the effect of corporate governance and firm characteristics on the extent of corporate social responsibility disclosure in sustainability report. Elements of corporate governance that are used to test are Independent Commissary proportion, foreign ownership proportion and institutional ownership proportion. Then, for the characteristics of firm using firm size, firm age and industry type.The population in this study was all companies listed on the Stock Exchange in 2009 until 2011. The sample was determined by the purposive sampling method and obtain 12 companies. Type of data used was secondary data obtained from www.idx.co.id and corporate websites. The method of analysis used is multiple regression analysis.Based on the results of multiple regression analysis with a significance level of 5%, the results of this study concluded that: (1) Independent Commissary proportion has no effect on CSR disclosure in the SR with the coefficient β is negative 0.855 and significance value 0.159> 0.05, ( 2) foreign ownership proportion has no effect on CSR disclosure in the SR with the coefficient β is negative 0.001 and significance value 0.647> 0.05, ( 3) institutional ownership proportion has no effect on CSR disclosure in the SR with the coefficient β is negative 0.002 and significance value 0.233> 0.05, (4) firm size has no effect on CSR disclosure in SR with the coefficient β is positive 0.001 and significance value 0.980 > 0.05, (5) firm age has a positive effect on CSR disclosure in SR with β coefficient is positive 0.021 and significance value 0.003> 0.05, and (6) industry tipe has a positive effect on CSR disclosure in SR with β coefficient is positive 0.385 and significance value 0.004.Keywords: Corporate Governance, Corporate Characteristics, CSR, Sustainability Report